Finding someplace - Patrick, Denise Lewis (Square Fish, 2016)
Thirteen-year-old aspiring fashion designer Reesie Boone is eagerly anticipating her birthday when she can finally sew her first outfit on Ma Maw's sewing machine. But Hurricane Katrina hits her city of New Orleans while Reesie is home alone, and she is forced to escape in a boat along with her elderly neighbor, Miss Martine. Although Reesie is finally rejoined with her family, they still have a long journey to undertake before they can return home.